ANALISA TINGKAT BAHAYA EROSI DI DAS ASAM-ASAM KABUPATENTANAH LAUT DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) - Beny Ristanto; Eko Rini Indrayatie; Khairun Nisa (Universitas Lambung Mangkurat, 2020)
This research was conducted from July to August 2018 in the Asam-asam watershed in Tanah Laut Regency. This study aims to calculate the rate of erosion using the USLE (Universal Soil Loss Equation) equation and determine the level of erosion hazard with the Geographic Information System (GIS) approach. The results show there are 82 units of land units with erosion ranges of 0.052 tons / ha / year up to 1,769,139 tons / ha / year. The biggest erosion rate is found in Latosol soil with steep slope and open soil moisture cover (LCTT) which is equal to 1,769.139 tons / ha / year. While the smallest erosion rate is found in latosol soil with flat slope and primary forest land cover (LDHP) which is equal to 0.052 tons / ha / year. In general, the Asam-asam Watershed has the Erosion Hazard Level (TBE) Criteria from low to very high. Erosion Hazard Level (TBE) in the Asam-Asam watershed with the criteria of low TBE has an area of 30,544.66 ha (61.38%), then the criteria for medium TBE are 13,870.56 ha (27.87%), then on the criteria high TBE is 2,636.10 ha (5.30%), and the criteria for TBE are very high, covering an area of 2,710.37 ha (5.45%). Judging from all the land units, the Asam-Asam watershed is dominated by low TBE criteria, while the lowest TBE criteria are found in the criteria of high and very high TBE.Keywords: Erosion, Asam-asam watershed , USLE, Geographic Information System